Faktor-Faktor Yang Mempengaruhi Staf Pengajar Di Institusi Pendidikan Tinggi Untuk Menggunakan Multimedia - Rinaldi rinaldi; Efrizon efrizon (Teknik Elektro Politeknik Negeri Padang, 2014)
This study is a descriptive study of the application towards multimedia that conducted in higher institution, West Sumatera with the objectives of assessing the factors affecting multimedia application in higher institution lecturers. It employed a survey questionnaire to collect respondents’ responses by using Likert-5 point type scales. It was conducted on 250 lecturers by using stratified random sampling from three types of higher institutions. Data collected and analyzed by using Statistical for the Social Sciences 19.0 (SPSS 19.0). Descriptive analysis shows that factors affecting multimedia application are limited amount of equipments, less support from the institution, no confidence in using multimedia for teaching, damaged equipments, insufficient time to prepare multimedia-based teaching materials, not enough salaries to assist in carrying out their duties properly, increased teaching workloads, ineffective multimedia training and no rewards or incentives from the institution for using multimedia in teaching. As conclusion, this study can be used by the relevant authorities to take action in improving education.